2022
DOI: 10.2478/aoas-2021-0043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of encapsulated Cosmos caudatus leaf extract on the physiological conditions, immune competency, and antioxidative status of broilers at high stocking density

Abstract: The present study aimed to investigate the effect of encapsulated Cosmos caudatus leaf extract on the physiological conditions, immune competency, and antioxidative status of broiler chickens raised at a high stocking density. After 15 days of rearing, 370 Lohmann broiler chicks were assigned to five treatment groups, including T0 (chicks were raised at a density of 10 birds/m2 and received no additive), T1 (chicks were raised at a density of 16 birds/m2 and received no additive), T2 (chicks were raised at a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Results from the present study indicated that there was neither linear nor quadratic trends for all haematological parameters in response to varying stocking densities. This contradicts Agusetyaningsih et al [ 25 ] who found that a higher stocking density (16 birds/m 2 ) resulted in higher levels of erythrocytes and haematocrits than a lower stocking density (10 birds/m 2 ). In the current study, the concentration of serum glucose was higher in birds raised at lower stocking densities than in those reared at higher stocking densities.…”
Section: Discussionmentioning
confidence: 70%
“…Results from the present study indicated that there was neither linear nor quadratic trends for all haematological parameters in response to varying stocking densities. This contradicts Agusetyaningsih et al [ 25 ] who found that a higher stocking density (16 birds/m 2 ) resulted in higher levels of erythrocytes and haematocrits than a lower stocking density (10 birds/m 2 ). In the current study, the concentration of serum glucose was higher in birds raised at lower stocking densities than in those reared at higher stocking densities.…”
Section: Discussionmentioning
confidence: 70%
“…The antibodies against NDV were measured using the hemagglutination inhibition (HI) technique and presented as a geometric mean (Log2). The levels of superoxide dismutase (SOD) and malondialdehyde (MDA) were determined as described by Agusetyaningsih et al [ 11 ]. The SOD was investigated based on the samples’ ability to reduce pyrogallol autoxidation, while a thiobarbituric acid (TBA) reactive material test was used to determine MDA.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was centrifuged at 3,500 rpm for 10 minutes to separate plasma and serum. MDA activity was measured by the reactive substances assay method for thiobarbituric acid (TBA) based on the method of Agusetyaningsih et al (2022). MDA concentration is expressed in units of nmol/ml.…”
Section: Sampling and Analysesmentioning
confidence: 99%
“…The reaction began with the addition of pyrogallol with a final concentration of 0.2 mM and then the absorption value was calculated kinetically. The SOD concentration is in units of U/ml (Agusetyaningsih et al, 2022).…”
Section: Sampling and Analysesmentioning
confidence: 99%